2018
DOI: 10.3390/cancers10100389
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Tumor-Infiltrating Leukocyte Scoring for Prognosis of Resected Hepatocellular Carcinoma Patients

Abstract: Liver resection is a curative treatment for hepatocellular carcinoma (HCC). Tumor-infiltrating leukocytes (TILs) are important players in predicting HCC recurrence. However, the invasive margin could not be confirmed as relevant for HCC. The migration of immune cells into HCC may originate from intratumoral vessels. No previous study has examined perivascular (PV) infiltration. Tumors from 60 patients were examined. Immunohistochemistry was performed against CD3, CD8, CD20, and CD66b. TILs were counted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 50 publications
(70 reference statements)
0
28
0
Order By: Relevance
“…Finally, we showed that the QTiS algorithm for different tumor types described previously [39,69] retrieved relevant results to highlight the importance of peritumoral TILs in patients with PDAC. Results with colorectal cancer indicate that quantification of immune cell infiltration has the potential to become an integral part of the TNM classification of PDAC [70].…”
Section: Discussionmentioning
confidence: 63%
“…Finally, we showed that the QTiS algorithm for different tumor types described previously [39,69] retrieved relevant results to highlight the importance of peritumoral TILs in patients with PDAC. Results with colorectal cancer indicate that quantification of immune cell infiltration has the potential to become an integral part of the TNM classification of PDAC [70].…”
Section: Discussionmentioning
confidence: 63%
“…Counting was done according to the QTiS algorithm by Miksch et al [48,49,50,51] with the ImageJ software (Version 1.51h, National Institutes of Health, Bethesda, MD, USA). Briefly, after substraction of background, color deconvolution was performed, selecting example regions for the following spectra: background, hematoxylin, and AEC.…”
Section: Methodsmentioning
confidence: 99%
“…In the prognosis model of HCC, in terms of etiology, the prognostic model of hepatitis B correlated to HCC (PAGE-B, CU-HCC, GAG-HCC, and REACH-B for the development of HCC) must be established, 15,16 and in terms of treatment, it is more important to evaluate the prognosis of recurrence and survival after surgical resection. 17,18 However, in the whole HCC population, a tumor progression model for the evaluation of the clinical condition of patients with HCC is not available. In this study, we established a novel model for predicting HCC progression, and this model was compared with wellknown classic tumor models (TNM staging system,…”
Section: Discussionmentioning
confidence: 99%